UPDATING THE CONTENT OF HIGHER ECONOMIC EDUCATION IN UKRAINE AT THE END OF THE XX CENTURY - K.D. Tumanyan (Academy of Cognitive and Natural Sciences, 2004)
The article analyses the trends in development of higher éducation in Economies in Ukraine during the last decade of the XX century. It présents the innovations and improvements in curriculum of higher educational establishments, which trained specialists in the fïeld of Economies.